Enzyme-free glucose sensors with efficient synergistic electro-catalysis based on a ferrocene derivative and two metal nanoparticles. Issue 9 (10th February 2022) - Zhan, Tao; Feng, Xiao-Zhen; An, Qi-Qi; Li, Shiyong; Xue, Mingyue; Chen, Zhencheng; Han, Guo-Cheng; Kraatz, Heinz-Bernhard
Abstract : We exploit the ferrocene–glutathione conjugate Fc-ECG as electron transfer mediator and make use of gold electrodes that were modified with either copper or cobalt nanoparticles to give sensor surfaces that exhibit excellent catalytic activity of glucose oxidation. Abstract : Gold electrodes (GE) were modified by the deposition of copper nanoparticles (CuNPs) and cobalt nanoparticles (CoNPs), followed by drop-casting of the ferrocene derivative FcCO-Glu-Cys-Gly-OH (Fc-ECG), resulting in two enzyme-free electrochemical sensors Fc-ECG/CuNPs/GE and Fc-ECG/CuNPs/GE. The ferrocene-peptide conjugate acts as an effective redox mediator for glucose oxidation, while metal nanoparticles acted as non-biological sites for glucose oxidation. Field emission scanning electron microscopy (FESEM), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were carried out for characterization, while differential pulse voltammetry (DPV) was used for glucose quantification. Under optimized conditions, DPV shows a linear relationship between glucose concentration and the peak current. Both sensors showed a surprisingly high sensitivity of 217.27 and 378.70 μA mM −1 cm −2, respectively. A comparison to other glucose sensors shows a sensitivity that is 25 times higher. The sensors exhibit good reproducibility, stability, and repeatability. In injection experiments, recovery rates were 87.39–107.65% and 100.00–106.88%, respectively.